Representasi Interseksionalitas Gender dalam Meme ‘Jomok’ dan Implikasinya terhadap Literasi Digital Generasi Z - Frans Tory Damara Pradipta; Enda Maharani; Guntur Sumaryandi; Mari Lalang (Indonesian Journal of Innovation Multidisipliner Research, 2026)
This study examines the representation of gender intersectionality in “jomok” memes and its implications for the digital literacy of Generation Z. As part of digital culture, memes do not only function as entertainment but also carry constructed meanings related to social identities, particularly gender and sexuality. This research aims to analyze how “jomok” memes represent gender intersectionality and how they influence the understanding and digital literacy of Generation Z. A qualitative approach was employed, with data collected through a questionnaire distributed via Google Form to 30 respondents and visual analysis of meme content circulating on social media. The findings indicate that “jomok” memes represent the intersection of gender identities through ambivalent humor, functioning not only as entertainment but also as a medium that shapes social perceptions. The recurring appearance of specific characters across various meme formats forms a collective narrative that reinforces meaning within digital culture. Meanwhile, respondents demonstrate a relatively good level of digital literacy; however, it is not fully accompanied by critical interpretive skills in understanding the deeper meanings embedded in memes. This study concludes that “jomok” memes play a role in shaping perceptions of gender identity in digital spaces, highlighting the need to strengthen digital literacy that emphasizes not only technical skills but also critical analysis and reflective understanding of media content.